2017
DOI: 10.1172/jci.insight.92512
|View full text |Cite
|
Sign up to set email alerts
|

Delayed decompression exacerbates ischemia-reperfusion injury in cervical compressive myelopathy

Abstract: Degenerative cervical myelopathy (DCM) is the most common progressive nontraumatic spinal cord injury. The most common recommended treatment is surgical decompression, although the optimal timing of intervention is an area of ongoing debate. The primary objective of this study was to assess whether a delay in decompression could influence the extent of ischemia-reperfusion injury and alter the trajectory of outcome in DCM. Using a DCM mouse model, we show that decompression acutely led to a 1.5- to 2-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 79 publications
0
62
1
Order By: Relevance
“…According to the above-mentioned hypothesis and based on experimental and epidemiologic studies the current literature suggests that the increased age of the patient, any comorbidities, and the chronic compression of the cord are potential risk factors and should be so identified. Specifically, recent experimental studies in mice models suggest that delayed decompression can exacerbate reperfusion injury and is associated with ongoing enhanced levels of cytokine expression, microglial activation, and astrogliosis [10], while early decompression inhibits the expression of TNF-α [24]. Furthermore, an extensive epidemiologic international study, noticed that older patients with comorbidities accompanied with severe and long-term compression of the cervical spinal cord undergoing surgical decompression, had a poorer functional outcome according to modified Japanese Orthopaedic Association score [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the above-mentioned hypothesis and based on experimental and epidemiologic studies the current literature suggests that the increased age of the patient, any comorbidities, and the chronic compression of the cord are potential risk factors and should be so identified. Specifically, recent experimental studies in mice models suggest that delayed decompression can exacerbate reperfusion injury and is associated with ongoing enhanced levels of cytokine expression, microglial activation, and astrogliosis [10], while early decompression inhibits the expression of TNF-α [24]. Furthermore, an extensive epidemiologic international study, noticed that older patients with comorbidities accompanied with severe and long-term compression of the cervical spinal cord undergoing surgical decompression, had a poorer functional outcome according to modified Japanese Orthopaedic Association score [9].…”
Section: Discussionmentioning
confidence: 99%
“…By this case report, we support the hypothesis that the reperfusion injury can also be subacute (until 24 h following decompression) [8], especially in an elderly population with atherosclerotic vessels, chronic hypertension, and other comorbidities [9], rather than being exclusively acute as in the three previous cases. Furthermore, delayed decompression exacerbates ischemia-reperfusion in cervical compressive myelopathy [10]. Spine surgeons should be aware of this extremely rare complication, not only intraoperatively but also postoperatively, in order to recognize this potential disastrous complication early on.…”
Section: Introductionmentioning
confidence: 99%
“…This abnormality denotes prolonged compression of the cord leading to neuronal loss or myelomalacia and associated with poor outcome. Delayed decompression could exacerbate the reperfusion injury cascade as has been suggested in experimental study in mice [13]. In the previously reported 6 cases, four cases have hyperintense T2 signal area in the preoperative MRI.…”
Section: Discussionmentioning
confidence: 78%
“…Yang et al ( 1 ) reported that surgical decompression increased the expression of inflammatory cytokines, including TNF-α and IL-1β, in an animal model of chronic severe spinal cord compression. Similarly, Vidal et al ( 21 ) suggested that decompression led to a 1.5- to 2-fold increase in expression levels of inflammatory cytokines in a mouse model of DCM. It was also reported that delayed decompression aggravated ischemia-reperfusion injury, resulting in decreased neurological improvement compared with earlier intervention.…”
Section: Discussionmentioning
confidence: 91%
“…In another study, perioperative methylprednisolone treatment (30 min prior to decompression and 2 weeks after decompression at one dose of 30 mg/kg) reduced neurological deterioration caused by ischemia-reperfusion injury via its anti-inflammatory effect in a mouse model of DCM ( 22 ). In animal models, the levels of inflammatory cytokines such as TNF-α and IL-1β increased when decompression-associated spinal cord ischemia-reperfusion injury occurred, indicating that inflammatory cytokines may be considered as an important evaluation indicator of decompression-associated spinal cord ischemia-reperfusion injury ( 1 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%